Entrepreneurship in wood economy and a proposition for an entrepreneurial model - Kropivšek, Jože (Zbornik gozdarstva in lesarstva, 2009)
Entrepreneurship and entrepreneurial activity of the population are of key importance for economic development, creation of new jobs and rise of the public welfare level. Some general researches (for example GEM - Global Entrepreneurship Monitor) showed that the entrepreneurial potential in Slovenia has not been completely maximized. Considering the findings from the research into entrepreneurship in wood economy we can claim the same also for the domain of wood, since we discovered numerous opportunities that are not being used at the moment. Research was made in small wood-industry companies with the help of questionnaires. On the basis of the established facts, a modern, future and development-orientated entrepreneurial model was elaborated, which is based on internal and external factors of entrepreneurship efficiency. Entrepreneurial activity is based on constant, planned and goal orientated learning and transfer (and use) of this knowledge in the business process.
Keywords: lesarstvo; modeli; podjetništvo; razvoj; Slovenija